2014
DOI: 10.3138/ptc.2013-23
|View full text |Cite
|
Sign up to set email alerts
|

Examining Interrater Reliability and Validity of a Paediatric Cardiopulmonary Physiotherapy Discharge Tool

Abstract: Several of the items in the Paediatric CPT Discharge Tool demonstrate good IRR. The discharge tool is ready for further psychometric testing, specifically validity testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
2
7
1
Order By: Relevance
“…The inter-observer reliability for wheeze detection, expressed as the Fleiss Kappa coefficient, was moderate in our study, reflecting a higher inter-observer reliability than reported in most previous studies [ 17 , 28 – 30 ]. ROC analysis showed cut-off values of >2% for inspiratory and >3% for expiratory wheeze.…”
Section: Discussioncontrasting
confidence: 63%
“…The inter-observer reliability for wheeze detection, expressed as the Fleiss Kappa coefficient, was moderate in our study, reflecting a higher inter-observer reliability than reported in most previous studies [ 17 , 28 – 30 ]. ROC analysis showed cut-off values of >2% for inspiratory and >3% for expiratory wheeze.…”
Section: Discussioncontrasting
confidence: 63%
“…Some studies have evaluated patient wheezing in various clinical settings. 5,6 In our study, the setting in which auscultation was performed and interpreted was consistently the same.…”
Section: Discussionmentioning
confidence: 87%
“…The results of those studies may also have been influenced by the patients' environments and postural positions during auscultation. Some studies have evaluated patient wheezing in various clinical settings 5,6 . In our study, the setting in which auscultation was performed and interpreted was consistently the same.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This was reinforced by Jette, Grover and Keck (2003), who reported that when formulating discharge decisions, physiotherapists and occupational therapists consider the patient's preferences and needs, ability to participate in care, level of functioning and life context (Jette, Grover & Keck 2003). To assist physiotherapists with decision-making regarding discharge, there are multiple discharge tools available for different patient presentations (Lati et al 2014); however, it is acknowledged that each unique patient presentation must inform decisionmaking (Taylor et al 2010). Therefore, the complexity of decision-making relating to discharge planning (Frost 2001;Jette, Grover & Keck 2003;Taylor et al 2010) is considered an important area for pre-professional training and ongoing professional development (Frost 2001).…”
Section: Introductionmentioning
confidence: 99%